Ingestion of hypertonic NaCl vs. palatable drinks by sodium-depleted rats - Nozaki, P. N.; Pereira, DTB; Moura, F. V.; Menani, José Vanderlei [UNESP]; De Luca, L. A. (Elsevier B.V., 2002)
This work investigated whether the preference for NaCl solution is shifted to more palatable solutions in the adult male sodium-depleted rat (n=6-10 per group). Animals had daily access to three bottles, one containing water, another 1.8% NaCl (300 mM), and a third containing 0.9% NaCl (150 mM), Gatorade (orange-OG or grape flavored-GG), orange juice (sweetened or unsweetened, from concentrate), or 10% sucrose (no sodium). Sodium content in Gatorade and orange juice ranged from 7 to 14 mEq/l. Daily intakes were recorded for at least 5 days prior to sodium depletion. Then, the animals were depleted of sodium (diuretic plus sodium-deficient diet and water for 24 h). Then, the other two bottles were returned to the animals and the intakes were recorded for 120 min (sodium preference test, SPT). Daily intake from the third bottle (except for unsweetened orange juice) at least doubled the daily 1.8% NaCl intake. The average 1.8% NaCl intake (13 +/- 2 ml) in the SPT was higher than the intake of 10% sucrose (6 +/- 1 ml) or of any other solution (less than 6 ml). The intakes of 1.8% NaCl and 0.9% NaCl (10 +/- 3 ml) were similar during the SPT. The animals also preferred 0.9% NaCl (27 +/- 1 ml) to OG (3 +/- 1 ml) in the absence of 1.8% NaCl in the SPT. Therefore, the preference for sodium in sodium-depleted rats also applies when palatable and nutritive solutions are simultaneously available. (C) 2002 Elsevier B.V. All rights reserved.
Keywords: salt intake; sodium intake; taste; isotonic drinks; gatorade; orange juice; dehydration